The Body Composition Monitor: a flexible tool for routine fluid management across the haemodialysis population. (25th May 2017) - Keane, D F; Baxter, P; Lindley, E; Moissl, U; Pavitt, S; Rhodes, L; Wieskotten, S
Abstract: Bioimpedance measurements with the Body Composition Monitor (BCM) have been shown to improve fluid management in haemodialysis. However, there is a lack of a sufficiently robust evidence-base for use of the BCM outside of standard protocols. This study aims to define the error associated with BCM measurement using alternate paths and timings to allow the use of BCM with confidence in a range of clinical scenarios. BCM measurements were made in 48 healthy controls and in 48 stable haemodialysis patients before and immediately after dialysis. The effect of utilising alternative measurement paths was assessed using mixed effects models and the effect of measuring post-dialysis was assessed by comparing changes in BCM-measured overhydration (OH) with weight changes over dialysis. The data from healthy controls suggest that there is no difference in BCM-measured OH between all the whole-body paths other than the ankle-to-ankle measurement. Dialysis patients showed similar results other than having higher BCM-measured OH when measured across the site of a vascular access. There was good agreement between BCM-measured OH from the standard path and change in weight, suggesting post-dialysis measurements can be utilised. These results suggest BCM protocols can be flexible regarding measurement paths and timing of measurement to ensure as many patients as possible can benefit from the technology.